Labor Market Policies and Unemployment in Morocco : A Quantitative Analysis - Agenor, Pierre-Richard; El Aynaoui, Karim (World Bank, Washington, DC, 2014)
The authors study the impact of labor market policies on unemployment in Morocco. They begin by reviewing the main features of the labor market. Then they present a quantitative framework that captures many of these features-such as a large public sector, high redundancy payments, powerful trade unions, and international labor migration. The authors simulate the impact of a cut in the minimum wage and a reduction in payroll taxation. The results indicate that these policies may have a significant impact in the short term on open unskilled unemployment. But they also show that labor market reforms, to be effective in the long run, may need to be accompanied by offsetting changes in the budget to avoid crowding-out effects on private investment.